Berbamine, a bioactive alkaloid, suppresses equine herpesvirus type 1 in vitro and in vivo - Li, Zeyu; He, Yuanxiu; Ge, Lijuan; Quan, Ran; Chen, Junzhen; Hu, Yue; Sa, Ruixue; Liu, Jianhua; Ran, Duoliang; Fu, Qiang; Shi, Huijun (Frontiers in Veterinary Science, 2023)
Equine herpesvirus type 1 (EHV-1) poses a global threat to equines. The anticancer agent berbamine (BBM), a bioactive alkaloid, has been shown to inhibit viral infection. However, whether BBM can inhibit EHV-1 infection remains unclear. This study investigated the effect of BBM treatment on EHV-1 infection. Quantitative PCR (qPCR), immunoblotting, the Reed-Muench method, and pathological examination were employed to study the ability of BBM to inhibit EHV-1 infection, viral DNA replication, viral protein production, virion secretion, and cytopathogenesis in vitro and in vivo. The in vitro studies revealed that 10 μM BBM effectively suppressed EHV-1 viral entry into cells, viral DNA replication, and virion secretion, while the in vivo studies verified the ability of BBM to suppress EHV-1-induced damage of brain and lung tissues and animal mortality. These findings strongly suggest that BBM could be a serious contender in the therapeutic control of EHV-1 infection of equines.